The Android Application “Haji Pintar” And Independent Pilgrimage - Malik, Hatta Abdul; Sulistio, Sulistio; Jarong, Koree (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This article aims to find out the usability of the